Financial aspects of a national income-related pension scheme - Honohan, W. A. (Statistical and Social Inquiry Society of Ireland, 1977)
The cost of the three model schemes was estimated on the assumption that all employees would be specifically covered; it was taken that no groups of employees would be specifically exempted or excluded. Moreover, although it is still an open question whether provision will be made for the contracting-out, or partial contracting-out, of those who are satisfactorily covered in occupational or other pension schemes, the costs shown in the Green Paper do not take account of any such possibility. Self-employed classes are not included.
Symposium on the Government Green Paper "A National Income-Related Pension Scheme"
Read before the Society, 16 December 1976
Keywords: Irish pensions policy; A National Income-Related Pension Scheme; Social insurance; 314.15